Pengaruh Astaxantine Oral terhadap Kadar Serum Tumor Necrosis Factor Alpha pada Pasien Akne Vulgaris-lores - Reti Anggraeni; Niluh Widjayanti; Harijono Kariosentono; Indah Julianto; Endra Yustin; Muhammad Eko Irawanto; Prasetyadi Mawardi (PT Dexa Medica, 2020)
Background: Acne vulgaris (AV) is chronic inflammatory disease affecting the pilosebaceous unit manifested as closed and open comedones, papules, pustules, and nodules. Treatment of AV generally involves more than one drug due to multifactorial pathogenesis. Objective: This study aims to determine the efficacy of 4 mg oral astaxanthin as an adjuvant AV therapy in decreasing serum level of inflammatory marker tumor necrosis factor alpha (TNF-α). Method: This is a double-blind randomized controlled trial. Subjects were 34 patients with mild and moderate AV (Global Acne Grading System/GAGS 1-30) that were treated with combination of tretinoin 0.025% and clindamycin phosphate 1.2%. Astaxanthin was added to the treatment group and lactulose as placebo was added to the control groups, given for 4 weeks. The pretest and posttest results in both groups were analyzed statistically using nonparametric test. Results: Decrease in TNF-α serum levels occurred in both groups but significant difference compared to baseline were only found in treatment group (p=0.015). There was no significant difference in the reduction of TNF-α levels between both groups (p=0.459). Conclusion: Although the results did not show a significant difference overall, but in the treatment group, astaxanthin can significantly lower TNF-α serum levels compared to baseline.